2017
DOI: 10.1021/acsami.7b04602
|View full text |Cite
|
Sign up to set email alerts
|

Laminated and Two-Dimensional Carbon-Supported Microwave Absorbers Derived from MXenes

Abstract: Microwave absorbers with layered structures that can provide abundant interfaces are highly desirable for enhancing electromagnetic absorbing capability and decreasing the thickness. The atomically thin layers of two-dimensional (2D) transition-metal carbides (MXenes) make them a convenient precursor for synthesis of other 2D and layered structures. Here, laminated carbon/TiO hybrid materials composed of well-aligned 2D carbon sheets with embedded TiO nanoparticles were synthesized and showed excellent microwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
172
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 339 publications
(178 citation statements)
references
References 50 publications
6
172
0
Order By: Relevance
“…The magnetic permeability is omitted because both MXene and PI are nonmagnetic, and thus the MXene materials attenuate microwave mainly by the dipolar polarization induced by the surface terminations, localized defects, and dangling bonds, which has been systematically studied by Han et al Interestingly, the lightweight aerogel has a large dielectric loss tangent (tan δ e = ε″/ε′) of 0.39, which is comparable to the reported powdery MXene‐based materials with much higher loadings. [24a,b,25] Generally, the frequency bandwidth of reflection loss ≤−10 dB is considered as the effective absorption bandwidth (EAB). For the MXene/PI aerogel (8.9 mg cm −3 , ≈4.0 S m −1 ), a maximum reflection loss of −45.4 dB is achieved at 9.59 GHz (3 mm) and the EAB reaches up to 3.7 GHz (8.3–12.0 GHz), which almost cover the whole X‐band (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic permeability is omitted because both MXene and PI are nonmagnetic, and thus the MXene materials attenuate microwave mainly by the dipolar polarization induced by the surface terminations, localized defects, and dangling bonds, which has been systematically studied by Han et al Interestingly, the lightweight aerogel has a large dielectric loss tangent (tan δ e = ε″/ε′) of 0.39, which is comparable to the reported powdery MXene‐based materials with much higher loadings. [24a,b,25] Generally, the frequency bandwidth of reflection loss ≤−10 dB is considered as the effective absorption bandwidth (EAB). For the MXene/PI aerogel (8.9 mg cm −3 , ≈4.0 S m −1 ), a maximum reflection loss of −45.4 dB is achieved at 9.59 GHz (3 mm) and the EAB reaches up to 3.7 GHz (8.3–12.0 GHz), which almost cover the whole X‐band (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…5 Overall, the conductivity of amorphous carbon is moderate as compared to other carbon materials like graphene, graphite etc. [6][7][8] Based on this consideration, amorphous carbon has a huge potential for combating the serious electromagnetic interference issue (EMI) if serving as an electromagnetic absorber. 9 In recent years, the rapid development of electronic, wireless communication techniques has resulted in increasing levels of electromagnetic pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2D transition metal carbide (MXene) has shown excellent shielding performance in the microwave regime . Among all, a thin film of Ti 3 C 2 T x MXenes (≈1.5 µm) can block 99.99% EM waves showing the highest EMI shielding efficiency (EMI SE) for materials of comparable thicknesses . Han et al reported a composite of Ti 3 C 2 T x in wax which delivers an EMI SE value of 76.1 dB with a thickness of only 1 mm .…”
mentioning
confidence: 99%